Evaluation of Hospital Information Management System (HIMS) by using the method Coping Model of User Adaption (CMUA) at the Siti Khodijah Sepanjang Hospital - Syifa Kania Mumtaz; Cholifah Cholifah; Umi Khoirun Nisak (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The Siti Khodijah Muhammdiyah Sepanjang Hospital uses EHOS as a means of providing HIMS. Preliminary study found that in outpatient units consisting of 30 clinics, 1 clinic did not record on the EHOS application, namely home care in filling out data, it was known that filling was still incomplete on patient identity sheets, general consent, initial assessment, and special examinations. The porposed this study to improve the utilization of HISM technology at siti khodijah sepanjang hospital based on the CMUA method using a sample of 135 respondents determination of the number of samples used the formula estimate a proportional in finite population with minimal 117 samples. Simple random sampling was used. This study was conducted from September to December 2022 at Siti Khodijah Sepanjang Hospital. The results of this study are 8 hypotheses, most of which have significant value, including H1: the perception of using HIMS as an opportunity (PO) will positively influence the adoption of a benefit-maximizing strategy (BM) of significant value (sig.0.007). H2: the perception of using HIMS as an opportunity (PO) will positively influence the adoption of a benefit satisfaction strategy (BS) with significant value (sig. 0.00). H3: The manager's perception of the use of HIMS as a threat (PT) will positively influence the disturbance management strategy (DH), with a significant value (sig. 0.000). H5: when managers perceive a situation as an opportunity, the more control they feel over the benefits of HIMS, the more likely they are to adopt a benefit maximizing (BM) strategy of significant value (sig. 0.000). H6: When managers perceive a situation as an opportunity, the more control they feel over the benefits of HIMS, the more likely they are to adopt a significant value benefit satisfaction (BS) strategy (sig. 0.016). H7: when a manager perceives the use of HIMS as a threat, the greater the perceived control over the implementation of security measures, the more he or she will adopt an intrusion management strategy (SP) of significant value (sig. 0.004). It was concluded that in using HIMS to optimize its use from the perspective of threats and opportunities, managers can adopt benefit maximizing strategies, benefit satisficing strategies, and disturbance handling strategies.